Lecturers’ perspectives on how introductory economic courses address sustainability (2015)
Purpose The purpose of this article is to explore sustainability commitments’ potential implications for the curriculum of introductory economics courses. Universities have signed the Talloires Declaration, committing themselves to promoting students’ environmental literacy and ecological citizenship, thereby creating pressure to integrate sustainability across the curriculum. Design/methodology/approach A case study approach involving qualitative research methods and the three largest public universities in British Columbia, Canada, was used. As one component of a larger study, 11 of the 19 economists who delivered the course over the study period were interviewed. The theoretical framework was informed by ecological economics scholarship on how mainstream economic thought represents environment-economy linkages. Findings Findings suggest that universities’ sustainability commitments have not influenced principles of economics curriculum. Sustainability is not salient to lecturers; prospects that mainstream economics departments will integrate sustainability into curriculum in a timely manner without external pressure appear limited. Practical implications While institutions often enthusiastically report on courses that contribute to students’ ecological literacy, identifying curriculum that may confound student understanding of sustainability receives less emphasis. Introductory economics courses appear to merit scrutiny from this perspective. Originality/value About 40 per cent of North American university students take an introductory economics course, relatively few take more advanced economics courses. This course, thus, teaches many students economic theory and the economics profession’s approach to evaluating public policy, and has potential to contribute to knowledge of sustainability. Few studies examine how undergraduate economics curriculum addresses sustainability.